COMMUNICATION STRATEGY IN GUIDANCE AND MANAGEMENT OF WASTE BUSINESS IN THE ENVIRONMENTAL SERVICE SERDANG BEDAGAI REGENCY - Sri Utami; Leylia Khairani; Faustyna (RADJA PUBLIKA, 2024)
This study aims to analyze the organizational communication strategy applied in the development and management of waste businesses by the Serdang Bedagai Regency Environmental Service. The main focus of this study is the communication strategy applied to improve understanding and cooperation between the government and business actors in the management of Hazardous and Toxic Materials (B3) waste. This study uses a qualitative method with a descriptive case study approach. Data were collected through in-depth interviews, observation, and documentation. Key informants in this study include Muhd ​​Arifin Pane, SP (Head of Waste Management), Supendi, S.AP. (Head of Waste Management Section), Sukawati, SP (Head of Hazardous and Toxic Materials Waste Section), and one waste business actor. The results of the study indicate that the organizational communication theory applied involves vertical communication between the government and business actors, which focuses on socialization and development. Barriers to communication include semantic, mechanical, and ecological barriers where business actors lack understanding of waste management in accordance with regulations, as well as minimal use of communication technology. This study concludes that a more participatory and integrative communication strategy is needed to increase business actors' awareness and compliance with waste regulations, as well as to create better relationships between the government and business actors.